Polythiophene-enhanced 2D carbon material based photoelectrochemical sensors - Tan, Adriel Yan Sheng (2025)
Photoelectrochemical (PEC) sensors are electrochemical sensors that detect various targets using visible light. Due to its robust detection and simple design, PEC sensors are suitable for detecting the targets of the following research: carbohydrate antigen 19-9 (CA 19-9) and iron (III) ions (Fe3+). The following thesis first reports the development of a PEC biosensor for the detection of CA 19-9, a biomarker commonly associated with pancreatic and colorectal cancer using graphitic carbon nitride/1-pyrenebutyric acid N-hydroxysuccinimide/polythiophene (GCN/PBASE/PTh). GCN, a photosensitive alternative to graphene has been widely explored as a photosensitive material for PEC sensors. In this work, GCN was modified with PTh, a conductive polymer and PBASE, a biolinker to form a composite. Material characterisations confirmed the formation of the composite, GCN/PBASE/PTh. The use of PTh improved the electrical response of GCN, while the introduction of PBASE has allowed further conjugation of the CA 19-9 antibody with the biosensor platform. The detection of CA 19-9 is through antigen-antibody interaction. Based on the electrical response of cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and chronoamperometry (CA), it is found that the sensor can detect CA 19-9 in the range of 50 – 1000 U/ml with the limit of detection (LOD) of 0.052 U/ml. Although this detection range is not suitable for clinical use, the biosensor can still monitor the levels of CA 19-9 in patients’ post-treatment. Besides pre-clinical applications, PEC sensors can also be used in heavy metal detection in water sources. The second part of this thesis reports the use of MXene/titanium oxide/polythiophene (MXene/TiO2/PTh) in the detection of Fe3+, commonly found in household pipelines. MXene, provides electrical conductivity, while TiO2 photosensitivity and PTh further enhance the electrical response of the composite. Material characterisations confirm the successful synthesis of the composite. The detection of Fe3+ is conducted through its reduction to Fe2+ by ascorbic acid (AA) in an electrolyte. The sensor performed at the range of 0.5 – 100 μM with an LOD of 0.073 μM. In addition, the sensor is capable of Fe3+ detection in lake and tap water samples with a 92.3 – 104.8% recovery. The sensor which can detect Fe3+ at a concentration lower than the allowable limit of 5.4 μM, provides a method for monitoring the quality of various water sources while safeguarding the public's health.